The robe of skulls - French, Vivian; Collins, Ross (London : Walker Books, 2007)
The sorceress Lady Lamorna has her heart set on a very expensive new robe, and she will stop at nothing--including kidnapping and black magic--to get the money to pay for it.
Keywords: Fairy tales; English Fiction